Eco-friendly particle boards from Triumfetta cordifolia stems: Adhesion with Aningeria altissima tannin and stabilization using natural rubber latex - Armel Edwige Mewoli; Azemafac Desmond Nkapleweh; Abel Emmanuel Njom; Jean Jalin Eyinga Biwôlé; Anatole Chengoue Mboyap; Augustine Demze Nitidem; Catherine Chrysalde Litet; Ernest Martial Angoa; Herman Lekane Assonfack; Michel Mbere Taoga; Fabien Betene Ebanda; Lucien Raymond Meva’a; et al. (Results in Materials)
This article presents the manufacturing of eco-friendly particle boards from Triumfetta cordifolia stems, bonded with a tannin-based resin from Aningeria altissima and stabilized with natural rubber latex. This combination aims to reduce the use of synthetic resins that emit formaldehyde, while improving the water resistance and mechanical properties of the boards. Four formulations were studied, with latex concentrations varying from 0 % to 15 %. The panels containing 15 % latex showed reduced swelling (17.3 %) after 24 h of immersion, compared to panels without latex (80.1 %), and a density that complies with medium-density board standards. The best flexural strength (20.6 MPa) was achieved with 5 % latex, while the addition of latex up to 15 % increased internal bonding, reaching 0.55 MPa, well above the standards for boards used in dry conditions. These results demonstrate the potential of tannin and latex-based bio-adhesives as an ecological alternative to synthetic resins, meeting industrial requirements and contributing to a circular economy in the composite materials sector. The results show that the tannin-based resin improves the mechanical strength and water resistance of the panels, with optimal performance observed at 5 % latex content. The internal bond strength increased significantly with tannin, reaching 0.55 MPa, exceeding industry standards for dry-use panels.